Factors associated with receipt of Tetanus, Diphtheria, and Acellular Pertussis Vaccine (Tdap) in mothers who deliver preterm - Shetal I. Shah; David Aboudi; Daniel B. Blatt (Hygeia Press di Corridori Marinella, 2023)
Background: Maternal Tetanus, Diphtheria, and Acellular Pertussis Vaccine (Tdap) vaccination is recommended to prevent pertussis in newborns. Preterm infants experience greater morbidity/mortality from pertussis. Data on Tdap receipt in mothers who deliver preterm is limited.  Objective: To assess characteristics associated with Tdap vaccination in mothers who delivery preterm.  Methods: Analysis of 2,778 mothers between 270/7-366/7 weeks gestation from the 2012-15 Rhode Island Pregnancy Risk Assessment Monitoring System (PRAMS) database. Tdap vaccination status was based on an affirmative response to the PRAMS question, "Did you receive a Tdap vaccination before, during or after your most recent pregnancy?" Variables assessed included: race/ethnicity, language, age, income, toxic habits, education, insurance status, marital status, and antenatal comorbidities. Rao-Scott chi-square test and logistic regression used for analysis. Reasons for non-immunization were described.  Results: Among preterm infants, maternal Tdap immunization rate was 87% (2,414/2,778), of which 57% were white. Hispanic mothers exhibited lower rates of immunization (23% vs. 39%, p < 0.03). Previous live birth was also associated with decreased Tdap vaccination (51% vs. 71%, p = 0.001). Immunization rate was higher in mothers who received influenza vaccine (73% vs. 48%, p < 0.001). In un-immunized mothers, 50% of providers did not offer vaccination. In adjusted analysis, receipt of influenza vaccine and the pregnancy being "wanted" were associated with higher odds of Tdap immunization in mothers who delivered preterm (odds ratio [OR], 95% confidence interval [CI]: 2.10 [1.05-4.24], 2.20 [1.16-4.18], respectively). Previous live birth (OR 0.46, 95% CI: 0.23-0.91) and marriage (OR 0.31, 95% CI: 0.11-0.87) were associated with decreased odds of Tdap vaccination.  Conclusion: Increased offering of Tdap may increase immunization rates. Among mothers who delivered preterm receipt of influenza vaccine and desired pregnancy are associated with increased odds of Tdap immunization. In this cohort, mothers with a previous live birth or who are married may represent unique risk for non-immunization and may require more targeted counseling related to Tdap immunization.